ANALISIS PENDAPATAN PETERNAK AYAM RAS PEDAGING POLA KEMITRAAN INTI –PLASMA (Studi Kasus Peternak Plasma PT.Genesis di Kecamatan Grabag Kabupaten Magelang Jawa Tengah) - Daryanto Daryanto; Suprapti Supardi; Endah Subekti (MEDIAGRO, 2015)
A broiler chicken meat producer that has some advantages including, rapid capital turnover rate and a short maintenance period ie within five weeks of broiler already be harvested and weighs 1.9 kg / head. This has encouraged many farmers who seek broiler farms. PT. Genesis is one of the broiler farms, which work closely with the farmers in the district through a partnership Grabag core-plasama. The partnership goal is to increase revenue, and increase both the scale of the company's businesses and farmers. The purpose of this study was to analyze the mechanism of partnerships undertaken in partnership plasma core, know the maintenance management (cultivation) of cattle in partnership nucleus-plasma, and calculates the income and value of the R / C ratio obtained in the plasma farmer-core partnership plasma. The research was conducted in partnership with farmers who farm company PT. Genesis. Nucleus location is in Taman Anggrek Unggaran Housing. Plasma breeders located in District Grabag, Magelang regency. The research was carried out for 1 month, ie in February and March 2013 which was designed as a case study, a total of 11 respondents breeders who partnered with PT. Genesis is currently in production. Data were collected by census method. The data used are primary data and secondary data. Maintenance of production data using the data on the plasma farmers February to March 2013 period (1 period). Analysis of the data used is descriptive analysis, revenue analysis, and analysis of R / C ratio. Results of the analysis showed that the income on the income earned period February to March 2013 were farmers Rp 3,332,844.97 per period. Analysis results Net B / C ratio showed 1.02 and BEP are at the point 66,524,262.00   Key words: partnership mechanism, plasma farmers, income, Net B / C ratio